2019
DOI: 10.3390/biom9080350
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Amyloid Beta (Aβ) Peptide on Blood Vessel Walls in the Damaged Brain after Transient Middle Cerebral Artery Occlusion

Abstract: It is well known that amyloid beta (Aβ) peptides are generated in blood vessels, released into the brain during thrombosis, and temporarily accumulate in this organ after injury. Here we demonstrate that 24 h after transient middle cerebral artery occlusion (tMCAO), one of the standard models of focal ischemic stroke, Aβ peptide accumulates in the brain, concentrating on the blood vessel walls. Because Aβ oligomers are known to induce significant damage to brain cells, they act as an additional damaging factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Saponins work by stimulating the formation of new cells, or called Growth Factor. Causing the multiplication and growth of blood vessel endothelial cells, vascular smooth muscle cells and fibroblasts, causing cellular growth which ultimately repair damaged blood vessel walls [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…Saponins work by stimulating the formation of new cells, or called Growth Factor. Causing the multiplication and growth of blood vessel endothelial cells, vascular smooth muscle cells and fibroblasts, causing cellular growth which ultimately repair damaged blood vessel walls [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a clinical study by Liu et al [ 5 ] demonstrated that patients with A β deposition experienced a more severe and rapid cognitive decline over 3 years after stroke/transient ischemic attack compared with subjects without AD-like A β deposition, and A β was associated with changes in multiple cognitive domains. Recently, Martins et al [ 6 ] have reported the acute accumulation of A β oligomers within 24 h in blood vessel walls including small capillaries and nearby brain tissues after cerebral I/R, and that such accumulation acts as a detrimental factor promoting brain damage. Additionally, the accumulation of toxic A β can produce swelling in astrocytes and their endfeet and also cause dysregulation of capillaries by acting on pericytes, influencing energy supply for neurons [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…A similar accumulation of Aβ around blood vessels in the skin of AD patients and generally in older patients was described many years ago ( 66 , 139 ). Moreover, we recently reported that Aβ immunofluorescence accumulated on blood vessel walls in the damaged part of the brain and on nearby astrocytes after middle cerebral artery occlusion ( 35 ). Temporary accumulation of Aβ in GFAP-positive astrocytic bodies and processes that formed clusters with specific small vessel-like structures was reported previously ( 29 , 140 143 ), see also review: ( 38 ).…”
Section: Aβ Is a Vital Defense Protein With Multiple Rolesmentioning
confidence: 99%